Coronary chronic total occlusion and bifurcation lesions, lessons from contemporary management: case report - Uribe-Londoño, Carlos Esteban (2020)
Coronary artery disease involving chronic occlusions and bifurcation lesions continues to be a challenge for the interventional cardiologist. The improvement in the techniques has allowed a higher success rate, however, the best intervention strategy is unknown in this subgroup of patients with chronic occlusions and associated bifurcation lesions. We present the case of a patient in whom, in an angiography for study of chest pain, a chronic total occlusion and a bifurcation lesion were evidenced and were successfully treated by coronary intervention.